Factors Related To The Timeliness Of Re-Injection Of Injectable Birth Control Acceptors 3 Months At Pratama Aulia Medika Clinic, Cirebon Regency - Febrilianti, Ega; Tonasih, Tonasih; Mutya Sari, Vianty; Nurhasanah, Nurhasanah (Ann Publisher, 2025)
Background. Family planning is an effort to measure the number and distance of children desired. Injectable contraceptives are a way to prevent pregnancy from occurring through hormonal injections. The failure of the injectable contraceptive method is caused by the delay of the acceptor to re-inject. The rate of inaccuracy in the re-visit of birth control injections at the Aulia Medika Primary Clinic is still high at 52.9%. Purpose. This study aims to determine the factors related to the timeliness of re-injection of injectable birth control acceptors for 3 months at the Aulia Medika Primary Clinic, Cirebon Regency in 2025. Method. This study uses analytical research. Observational research method with a cross sectional approach. The population was 191 acceptors who visited in the January-December 2024 period and a sample of 66 samples. The sampling technique proposes